Investigation of Indoor Polycyclic Aromatic Hydrocarbons (PAHs) in Rural Northeast China: Pollution Characteristics, Source Analysis, and Health Assessment - Bai, Li; Li, Chunhui (Buildings (Basel), 2022)
Due to the low winter temperatures in rural areas of Northeast China, biomass fuels are widely used for heating and cooking, resulting in increased concentrations of PAHs in rural indoor areas during the heating period and threatening human health. Therefore, exploring the pollution characteristics, source localization, and risk assessment of indoor PAHs in rural Northeast China is of great significance for improving rural indoor air quality. In this study, PAHs were collected from a residential building in rural Northeast China for one consecutive year (January 2020–December 2020), and their concentrations were determined to explore the distribution patterns and sources of PAHs to further assess the carcinogenic risk of PAHs to humans. The results of the study showed that the average concentration of indoor PAHs in rural areas during the heating period (93.02 ng/m3) was about 1.81 times higher than that of the non-heating period (51.26 ng/m3). The main sources of PAHs were mixed combustion of biomass and coal, motor vehicle emissions, and domestic waste combustion. The level of indoor PAHs pollution has posed a carcinogenic risk to the health of the rural population in the Northeast.